Lnc(ing)RNAs to the “shock and kill” strategy for HIV-1 cure - Boliar, Saikat; Russell, David G. (Molecular therapy. Nucleic acids, 2021)
The advent of antiretroviral therapy almost 25 years ago has transformed HIV-1 infection into a manageable chronic condition, albeit still incurable. The inability of the treatment regimen to eliminate latently infected cells that harbor the virus in an epigenetically silent state poses a major hurdle. Current cure approaches are focused on a “shock and kill” strategy that uses latency-reversing agents to chemically reverse the proviral quiescence in latently infected cells, followed by immune-mediated clearance of reactivated cells. To date, hundreds of compounds have been investigated for viral reactivation, yet none has resulted in a functional cure. The insufficiency of these latency-reversing agents (LRAs) alone indicates a critical need for additional, alternate approaches such as genetic manipulation. Long non-coding RNAs (lncRNAs) are an emerging class of regulatory RNAs with functional roles in many cellular processes, including epigenetic modulation. A number of lncRNAs have already been implicated to play important roles in HIV-1 latency and, as such, pharmacological modulation of lncRNAs constitutes a rational alternative approach in HIV-1 cure research. In this review, we discuss the current state of knowledge of the role of lncRNAs in HIV-1 infection and explore the scope for a lncRNA-mediated genetic approach within the shock and kill strategy of HIV-1 cure. [Display omitted] A cure for HIV-1 remains a formidable challenge in biomedical research. Recent evidence indicates critical roles for lncRNAs in HIV-1 infection. This review summarizes the current knowledge of the roles of lncRNAs in HIV-1 latency and explores the potential of lncRNAs as therapeutic targets for an HIV-1 cure.